Challenges and Opportunities of Digital Strategies in Culinary MSMEs in the Digital Era from an Islamic Perspective - Tanjung, Hafiz Yazid; Nurbaiti, Nurbaiti; Jannah, Nurul (IAIN Manado, 2025)
This study aims to analyze the digital strategies implemented by the culinary MSME Dimsum Qoqom to improve business performance in Tanjung Mulia Hilir, Medan based on Islamic values. Using a descriptive qualitative approach, this study explores how the integration of digital technology and Islamic ethical principles is operationalized to strengthen the MSME’s competitiveness in a rapidly evolving market. Data were collected through semi-structured interviews with owners and employees, direct observation of daily digital operations, and documentation of marketing content and customer engagement. The analysis was carried out using the Miles and Huberman interactive model. The findings indicate that Dimsum Qoqom has effectively implemented digital marketing through social media promotion, online ordering platforms (e.g., WhatsApp and e-commerce food delivery services), and cashless payment systems to improve customer convenience. Islamic values are practically applied in several business practices such as ensuring fairness in pricing, clearly disclosing product ingredients and halal certification for transparency, and providing community support through discounted packages during religious events as a form of social responsibility. A SWOT analysis reveals internal strengths in the form of strong halal positioning and a loyal Muslim customer base, alongside opportunities for digital market expansion. This study concludes that a synergy between digital strategies and Islamic ethical implementation offers a promising approach to improving competitiveness and ensuring sustainable growth for culinary MSMEs in the digital era.